Self-assembled two-dimensional layered oxide supercells with modulated layer stacking and tunable physical properties. (June 2019) - Li, L.; Boullay, P.; Cheng, J.; Lu, P.; Wang, X.; Steciuk, G.; Huang, J.; Jian, J.; Gao, X.; Zhang, B.; Misra, S.; Zhang, X.; et al.
Abstract: Layered materials, represented by graphene and transition metal dichalcogenides, have aroused significant research interest with the intriguing physical phenomena behind and enormous nanoscale device applications. Here, we report two types of novel modulated Bi-based layered supercell (LSC) structures via combined experimental and first-principles investigation. These two types of oxide-based LSC structures are prepared through self-assembly fabrication from both BiMnO3 and Bi2 NiMnO6 by pulsed lased deposition under well-controlled growth conditions. Both LSC structures are composed of alternative layer stacking of two sublattices along the film growth direction, i.e. sublattice 1 of Mn–O or Ni–Mn–O octahedral slab and sublattice 2 of Bi2 O2 or Bi3 O3 slab, respectively. Moreover, these two LSC structures can be tuned by changing the compositions of Bi–O sublattice from Bi2 O2 to Bi3 O3 for the same material system by precise control of growth conditions. The experimental characterizations reveal that these new LSCs with modulated layer stacking sequence results in tunable physical properties including robust room-temperature ferromagnetism and unique optical properties, which is well consistent with our first-principles electronic structure calculations. This work demonstrates the possibility of tuning layered oxide stacking by self-assembly thin film growth for designed material functionalities. The Bi-based LSC can be epitaxially grown on flexible mica substrate which is of great significance toward future flexible layered oxide–based electronic applications such as magnetic data storage.